Rancang Bangun Purwarupa Aplikasi Deteksi Dini Penyakit Jantung Berbasis Case Base Reasoning dengan Keamanan Data - Dr. Nur Afny Catur Andryani, S.Si., MSc.; Muhamad Femy Mulya; Surnanto Surnanto; M. Rizam Kusfandi (Teknik Informatika, 2021)
The prevalence of heart disease has been consistently increasing in five recent years. In average 15 out of 1000 people have heart disease. Currently heart disease becomes the second leading cause of death in Indonesia. Early detection will guide the appropriate treatments to increase recovery opportunity. In another hand, many healthcare facilities in Indonesia are not equipped with the cardiologist. It triggers many heart disease cases are late to handle due late detection. Thus, we propose web based early heart disease detection application prototype using Case Base Reasoning framework. It is intended to support small clinic or other healthcare facilities which have no cardiologist to provide early detection of heart disease. The application is equipped with data security to handle the data privacy of the patient. Based on the black box evaluation by the expert, it is concluded that all the provided features can be run functionally.